Extension study of the safety and efficacy of CLS-TA for treatment of macular oedema associated with non-infectious uveitis (MAGNOLIA). Issue 8 (12th March 2021) - Khurana, Rahul N; Merrill, Pauline; Yeh, Steven; Suhler, Eric; Barakat, Mark R; Uchiyama, Eduardo; Henry, Christopher Ryan; Shah, Milan; Wang, Robert C; Kapik, Barry; Ciulla, Thomas
Abstract : Purpose: To assess the extended efficacy and safety of suprachoroidal triamcinolone acetonide injectable suspension (CLS-TA) among patients with macular oedema (ME) secondary to non-infectious uveitis (NIU). Methods: Patients with uveitic ME were treated with suprachoroidal CLS-TA at baseline and week 12 of the Efficacy and Safety of Suprachoroidal CLS-TA for Macular Edema Secondary to Noninfectious Uveitis: Phase 3 Randomized Trial (PEACHTREE) study. Time to rescue was evaluated over 24 additional weeks for MAGNOLIA. Safety data, visual acuity and retinal central subfield thickness (CST) reduction were also evaluated. Of the 53 eligible patients (46 CLS-TA and 7 control), 33 patients were enrolled (28 CLS-TA and 5 control). Results: Over the entire 48-week period for PEACHTREE and MAGNOLIA, the median time to rescue therapy was 257 days versus 55.5 days for the CLS-TA and sham-control arms, respectively. Of 28 CLS-TA treated patients who participated in MAGNOLIA, 14 (50%) did not require rescue therapy through approximately 9 months after the second treatment. Among CLS-TA patients not requiring rescue, there was a mean gain of 12.1 letters and mean CST reduction of 174.5 µm at week 48. No serious adverse events related to study treatment were observed. Conclusion: Approximately 50% of patients did not require additional treatment for up to 9 months following the last CLS-TA administration.